A humidity compensation method for a temperature and humidity sensor. Issue 1 (1st May 2022) - Yang, Yuchuan; Liang, Xiuxiu; Hong, Ting; Li, Xin
Abstract: This paper introduces the method of humidity compensation in the temperature and humidity sensor to improve the measurement accuracy of humidity. The nonlinearity of humidity and humidity affected by temperature are compensated in circuit and data processing respectively. On the circuit, the sampling principle and the structure of the operational amplifier in the design are introduced. The data processing is mainly polynomial fitting of the chip test data by MATLAB software, so as to improve the humidity measurement accuracy. After the final fitting, the humidity error can reach ±1.5RH in the range of 10 °C to 50 °C.